Sosialisasi Safety Riding Bagi Dosen dan Mahasiswa STIE Ganesha - Fuad Gagarin Siregar; Aep Saefullah (Jurnal Nusantara Berbakti, 2024)
This community service endeavors to enhance the understanding, awareness, and proficiency in road safety among participants. The employed methods encompass socialization, counseling, lectures, Q&A sessions, presenting traffic case examples, and implementing practical transportation safety materials for 55 lecturers and students at STIE Ganesha. The outcomes of the initiative indicate that PKM activities effectively heightened participants' knowledge of driving safety, encompassing the recognition of institutional roles in the South Tangerang City Traffic Communication Forum. However, there is a need to enhance their comprehension of Law Number 22 of 2009. Successful socialization has augmented comprehension of safety riding, particularly among parents tasked with guiding their families to avert accidents. Preventive measures involve fostering public awareness, upgrading road infrastructure, enforcing traffic laws, and enhancing traffic safety education. This initiative demonstrates an amplified understanding among participants, particularly parents, concerning motorcycle driving safety after exposure to engaging and pertinent material.